The Effect of Diet on the Prevalence of Thyroid Disorder Among Libyans - Abuagela, Manal; Abdarazak Hakam; Fadua Abd-Alwafi; Shames Abuhalala (AlQalam Journal of Medical and Applied Sciences, 2025)
The thyroid gland’s function is crucial in regulating numerous vital functions, significantly influencing physical and mental development. Iodine, an essential micronutrient, is required in moderate amounts for optimal thyroid gland function, as it prevents enlargement and promotes the production of thyroid hormones T4 and T3. Disruptions in these hormones impact overall health, leading to conditions such as thyroid enlargement, cognitive deficiencies, and increased risk of breast cancer. In Libya, several preventive procedures, including providing iodized salt, were implemented to combat iodine deficiency, yet the prevalence of thyroid diseases continues to rise. This study investigates the importance of thyroid hormones, the critical role of iodine intake and dietary factors, and the prevalence of thyroid disorders among both men and women in Tripoli, Libya. In a randomly selected hospital, 900 visitors of various ages were assessed for T4, T3, and TSH levels using Chemiluminescence Immunometric Assays (CIA). The results indicated elevated thyroid hormone levels in 7.3% of women and 6.4% of men, while 0.8% of women and 0.2% of men exhibited low TSH levels. Notably, women demonstrated a 5 to 10 times higher susceptibility to thyroid issues compared to men, although the reasons for this disparity remain uncertain. Factors such as iodine intake, the estrogenic hormonal influence, and genetic variations affecting thyroid hormone synthesis may play contributing roles. In conclusion, enhancing the diagnosis and management of thyroid disorders in Libya requires targeted awareness campaigns, robust research endeavors, and collaborative healthcare initiatives to improve health outcomes and quality of life. وظيفة الغدة الدرقية بالغة الأهمية في تنظيم العديد من الوظائف الحيوية، مما يؤثر بشكل كبير على النمو البدني والعقلي. اليود، وهو عنصر غذائي دقيق أساسي، مطلوب بكميات معتدلة لوظيفة الغدة الدرقية المثلى، لأنه يمنع التضخم ويعزز إنتاج هرموني الغدة الدرقية T4 وT3. تؤثر الاضطرابات في هذه الهرمونات على الصحة العامة، مما يؤدي إلى حالات مثل تضخم الغدة الدرقية، والقصور الإدراكي، وزيادة خطر الإصابة بسرطان الثدي. في ليبيا، تم تنفيذ العديد من الإجراءات الوقائية، بما في ذلك توفير الملح المعالج باليود، لمكافحة نقص اليود، ومع ذلك يستمر معدل انتشار أمراض الغدة الدرقية في الارتفاع. تبحث هذه الدراسة في أهمية هرمونات الغدة الدرقية، والدور الحاسم لتناول اليود والعوامل الغذائية، ومعدل انتشار اضطرابات الغدة الدرقية بين كل من الرجال والنساء في طرابلس، ليبيا. في مستشفى تم اختياره عشوائيًا، تم تقييم 900 زائر من مختلف الأعمار لمستويات T4 وT3 وTSH باستخدام اختبارات الكيمياء المناعية (CIA). أشارت النتائج إلى ارتفاع مستويات هرمون الغدة الدرقية لدى 7.3% من النساء و6.4% من الرجال، بينما انخفضت مستويات هرمون TSH لدى 0.8% من النساء و0.2% من الرجال. والجدير بالذكر أن النساء أظهرن قابلية أعلى للإصابة بمشاكل الغدة الدرقية من الرجال بما يتراوح بين 5 و10 مرات، إلا أن أسباب هذا التفاوت لا تزال غير مؤكدة. وقد تلعب عوامل مثل تناول اليود، والتأثير الهرموني الإستروجيني، والاختلافات الجينية التي تؤثر على تخليق هرمون الغدة الدرقية دورًا مساهمًا. وختامًا، يتطلب تحسين تشخيص وإدارة اضطرابات الغدة الدرقية في ليبيا حملات توعية موجهة، وجهودًا بحثية حثيثة، ومبادرات رعاية صحية تعاونية لتحسين النتائج الصحية وجودة الحياة